2016
DOI: 10.1021/acs.iecr.6b03416
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel P/N/S-Containing Flame Retardant and Its Application in Epoxy Resin: Thermal Property, Flame Retardance, and Pyrolysis Behavior

Abstract: The combination of DOPO and 2-aminobenzothiazole (ABZ) was designed to develop P/N/S-containing flame retardant DOPO-ABZ, and its chemical structure was confirmed by HRMS, FTIR, and 1H and 31P NMR. The reduced thermal stability of EP/DOPO-ABZ formulations was found through DSC and TGA, as compared to that of EP. Fire properties were evaluated by LOI, UL-94, and cone calorimeter tests, respectively. The results indicated that DOPO-ABZ imparted flame retardance to EP, and that EP/7.5 wt % DOPO-ABZ passed the V-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(121 citation statements)
references
References 41 publications
1
119
0
1
Order By: Relevance
“…23,24 The The phosphorus-containing structures could produce PO free radicals to capture active free radicals such as H and hydrocarbon free radicals during combustion. 26 Generally, the result of Py-GC/MS is consistent with those of the TG-FTIR and CC tests.…”
Section: Flame Retardancysupporting
confidence: 75%
See 1 more Smart Citation
“…23,24 The The phosphorus-containing structures could produce PO free radicals to capture active free radicals such as H and hydrocarbon free radicals during combustion. 26 Generally, the result of Py-GC/MS is consistent with those of the TG-FTIR and CC tests.…”
Section: Flame Retardancysupporting
confidence: 75%
“…Besides, the rest of the P-Ar bonds continue to be degraded and rearranged, and some structures containing P are nally generated, which can capture active free radicals during the burning. 26 Furthermore, the three kinds of inammable volatile gases can reduce the oxygen content and capture active free radicals during combustion through the gaseous ame retardance mode, resulting in a superior ame-retardant efficiency of PP.…”
Section: Flame Retardancymentioning
confidence: 99%
“…According to the previous research, 2‐benzothiazolamine containing nitrogen and sulfur elements possessed certain flame‐retardant effect. Considering the amino group in the chemical structure of 2‐benzothiazolamine, it might be used for the preparation of Schiff base which was able to react with DOPO to synthesize reactive flame retardant.…”
Section: Introductionmentioning
confidence: 92%
“…EHC, defined as the ratio of HRR to mass loss rate, is an important parameter to evaluate the burning degree of the volatile species generated from the materials during combustion . Compared with the av‐EHC values of the pure PS, it was found that all A‐PS copolymers showed lower av‐EHC, which proved the existence of gas‐phase flame‐retardant effect of AC 2 NP 2 during combustion.…”
Section: Resultsmentioning
confidence: 99%